2019
DOI: 10.21121/eab.454115
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the evaluation criteria for agritourism via delphi and analytic hierarchy process methods: a case study in Turkey

Abstract: The population is decreasing in the regions where agricultural lands are prevalent, agricultural areas are not used effectively and efficiently, and both the afore-said regions and the people living there show a recession with each passing day in terms of economic, social and cultural aspects. This study examines from a different perspective the agritourism, which can be considered as an alternative option for rural development. Accordingly, the main objective of the study is to determine and weight the evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Satriawan et al (2015) clarified the role of government support in creating job opportunities in agritourism through the role of government institutions in supporting farm owners and motivating them to exploit all agricultural resources in providing new tourism products and services that diversify their incomes and at the same time create more job opportunities for existing individuals who serve the visitor. As McGehee et al (2007) and Uludağ & Erdoğan (2019) argued the policies and government support provided to farm families contributed to their search to diversify their agricultural activities and develop new activities for their farms, which need more labor. Similarly, the results indicated that government support is significantly and positively linked with handicraft sales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Satriawan et al (2015) clarified the role of government support in creating job opportunities in agritourism through the role of government institutions in supporting farm owners and motivating them to exploit all agricultural resources in providing new tourism products and services that diversify their incomes and at the same time create more job opportunities for existing individuals who serve the visitor. As McGehee et al (2007) and Uludağ & Erdoğan (2019) argued the policies and government support provided to farm families contributed to their search to diversify their agricultural activities and develop new activities for their farms, which need more labor. Similarly, the results indicated that government support is significantly and positively linked with handicraft sales.…”
Section: Discussionmentioning
confidence: 99%
“…Many farming families tended to diversify agricultural production to preserve their farms due to many factors, such as climate changes, low incomes, dependence on natural products, and environmental pressures. Government policies also played a role in those families' search for agricultural diversification (McGehee et al, 2007;Uludağ & Erdoğan, 2019). Agritourism activities are visible on farms whose owners seek to reduce the decline in their income, diversify sources of income, and deal with crises and problems in the surrounding environment, such as fluctuations in agricultural markets or climate changes (Brune et al, 2023).…”
Section: Literature Review and Hypothes Es Development Agritouris Mmentioning
confidence: 99%
“…The green environment is made up of flowers, native plants, forests, wildlife, and all kinds of biodiverse natural features, different from lands dedicated to agriculture (Flanigan et al, 2015;Gao et al, 2014). In the research carried out by Uludağ and Erdoğan (2019), the highest criteria are given to this aspect, followed by cultural and historical values, agricultural use of the land, among others.…”
Section: Discussionmentioning
confidence: 99%
“…The agritourism experience and its accessories vary according to the regions, depending on the type of climate, environment, customs, agriculture, livestock production, among others. In some parts of the world, agritourism can focus on the experience of wine and vineyards (Back et al, 2020), pulque (Macfarland et al, 2019), tea gardens (Bhatta 2020), of beekeeping (Gandhy et al, 2019), of cattle, goats or sheep (Uludağ and Erdoğan 2019), among others. Likewise, in regions where the experience is allowed, it can be complemented with activities such as bow hunting (Varmazyari et al, 2018), eagle hunting (Kenebayeva 2014), horseback riding, use of different types of agricultural machinery, among others.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation